PENERAPAN TERAPI KOGNITIF UNTUK REMAJA YANG MENGALAMI FOBIA SOSIAL: SEBUAH KAJIAN KEPUSTAKAAN [IMPLEMENTATION OF COGNITIVE THERAPY TO ADOLESCENT WITH SOCIAL PHOBIA: A LITERATURE REVIEW] - Fani Rama Kapailu; Indah Farih Ululi; Muhammad Reza Ginanjar Mukti; A. Said Hasan Basri (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
Adolescence is a period where a person is looking for identity, namely by communicating and establishing social relationships and this period is a period of many changes which must be faced, especially social problems. However, some teenagers experience social phobia in the search for identity and experiencing these social relationships. Adolescents with social phobia are afraid to do or say things that are embarrassing or that would make them feel humiliated. For this reason, a treatment is needed so that it can reduce the social phobia that the teenager has. The purpose of this paper is to determine cognitive therapy in dealing with social phobia experienced by adolescents. The findings of this study are cognitive therapy is a therapy that is used in counseling related to individual (client) thoughts that are irrational and thus turn them into rational thoughts. Cognitive therapy is suitable for individuals who have social phobia disorder